Lipid Peroxide-Derived Reactive Carbonyl Species as Mediators of Oxidative Stress and Signaling - Biswas, Md. Sanaullah; Mano, Jun’ichi (Frontiers in Plant Science, 2021)
Oxidation of membrane lipids by reactive oxygen species (ROS) or O2/lipoxygenase leads to the formation of various bioactive compounds collectively called oxylipins. Reactive carbonyl species (RCS) are a group of oxylipins that have the ,-unsaturated carbonyl structure, including acrolein and 4-hydroxy-(E)-2-nonenal. RCS provide a missing link between ROS stimuli and cellular responses in plants via their electrophilic modification of proteins. The physiological significance of RCS in planta has been established based on the observations that the RCS-scavenging enzymes that are overexpressed in plants or the RCS-scavenging chemicals added to plants suppressed the plants' responses to ROS, i.e., photoinhibition, aluminium-induced root damage, programmed cell death, senescence, abscisic acid-induced stomata closure, and auxin-induced lateral root formation. The functions of RCS are thus a key to ROS- and redox-signaling in plants. Chemical species involved in distinct RCS signaling/damaging phenomenona were recently revealed, based on comprehensive carbonyl determinations. In this review, we present an overview of the current status of research regarding RCS signaling functions in plants, and we discuss present challenges for gaining a more complete understanding of the signaling mechanisms.